The Different Roles of miRNA-92a-2-5p and let-7b-5p in Mitochondrial Translation in db/db Mice - Huaping Li; Beibei Dai; Jiahui Fan; Chen Chen; Xiang Nie; Zhongwei Yin; Yanru Zhao; Xudong Zhang; Dao Wen Wang (Elsevier, 2019)
Excessive reactive oxygen species (ROS) generated in mitochondria is known to be a causal event in diabetic cardiomyopathy. Recent studies suggest that microRNAs (miRNAs) are able to translocate to mitochondria to modulate mitochondrial activities, but the roles of such miRNAs in diabetic cardiomyopathy remain unclear. We observed a marked reduction of mitochondrial gene cytochrome-b (mt-Cytb) in the heart of db/db mice compared with controls. Downregulation of mt-Cytb by small interfering RNA (siRNA) recaptured some key features of diabetes, including elevated ROS production. Microarray revealed that none of the miRNAs were upregulated, but 14 miRNAs were downregulated in mitochondria of db/db heart. miR-92a-2-5p and let-7b-5p targeted mt-Cytb and positively modulated mt-Cytb expression. Re-expression of miR-92a-2-5p and let-7b-5p into cardiomyocytes led to reduced ROS production. Furthermore, recombinant adeno-associated virus (rAAV)-mediated delivery of miR-92a-2-5p, but not let-7b-5p, was sufficient to rescue cardiac diastolic dysfunction in db/db heart. Let-7b-5p not only upregulated mt-Cytb in mitochondria, but also downregulated insulin receptor substrate 1 in cytosol and finally lead to no efficiency for improvement of diastolic dysfunction in db/db mice. Our findings demonstrate that reduced mitochondrial miRNAs contribute to impaired mitochondrial gene expression and elevated ROS production. Re-expression of miR-92a-2-5p enhances mitochondrial translation and reduces ROS production and lipid deposition, which finally rescues diabetic cardiomyopathy. Keywords: diabetic cardiomyopathy, mitochondrial miRNAs, diastolic dysfunction, mitochondrial Cytb